EFEITO DO AMBIENTE SOBRE AS CARACTERÍSTICAS DE DESEMPENHO, CARCAÇA, ÓRGÃOS E TEMPERATURAS CORPORAIS DE CODORNAS EUROPEIAS - BONFIM, Dihego Silva (2015)
The objective was to evaluate the effects of environmental/consumption temperature on performance, carcass yield, sections and organs and body temperatures of quails of 14 to 42 days old. 450 quails (Coturnix coturnix coturnix) were distributed in batteries, packed in two masonry rooms, with one their containing an air conditioner for chill the environment. The design was completely randomized with three treatments and six replicates of 25 birds, totaling 18 experimental units. The treatments consisted in: 26AL (26°C Ad libitum feeding); 32AL (32°C feeding Ad libitum) and 26PF (26°C feeding controlled to maintain the same consumption of quails kept at 32°C). Were evaluated the intake of feed (FI), weight gain (WG), feed conversion (FC), body weight (W28d, W42d) and energy efficiency to weight gain (EEWG) in quails in the initial period (14 to 28 days) and cumulative (14 to 42 days). At 28 and at 42 days, the carcass weight (CW), the yields (%) carcass (CY), breast (BY), thigh (TY), drumstick (DY) and wing (WY); the relative weights (%) of the digestive tract (RWDT), heart (RWHEA), liver (RWLIV), gizzard (RWGIZ) and intestine (RWINT). Also were evaluated the temperatures (°C) cloacal (CT) and surface (head, HET; breast, BT; back, BAT, wing, WT, and leg, LET) and the temperatures (°C) average surface (AST) and body average (ABT), at 28 and 42 days, in three hours (7:00, 13:00 and 19:00h). The treatment means were compared by SNK test considering the 5% level of significance. The quails of the 32AL group present decreased (P<0.05) of the FI, WG, W28d, W42d in relation to those of the 26AL group, with no difference (P>0.05) in the FC and EEWG. Already to those of 26PF group worsened (P<0.05) the FI, WG, FC, W28d, W42d and EEWG in relation those of the 26AL group. Worsened (P<0.05) in the GP, CA, P28d and EEGP of the birds of 26PF group in relation to those of the 32AL group in the initial period, with no difference (P>0.05) between these variables in the accumulated period. It was observed reduction (P<0.05) in the CW of the quails of groups 32AL and 26PF in relation to those of the 26AL group, there not effects (P>0.05) on the CY and sections. It was observed effect (P<0.05) of the environment/consumption about the RWHEA (28 days) and about the RWGIZ (42 days), there was no effect (P>0.05) about the RWDT, RWINT and RWLIV. The CT, WT at 28 days (07:00 and 13:00h) and the LET at 42 days (7:00h), were not influenced (P>0.05) by the environment/consumption. The quails of the 32AL group presented HET, BT, BAT and higher AST (P<0.05) to those of the groups kept at 26°C, at all hours. The ABT of birds of 32AL group was higher (P<0.05) in relation to birds kept at 26°C, at 28 (13:00h) and 42 days (07:00, 13:00 and 19:00h). The environment 32°C favors the performance of quail to 28 days, hurting from that age compared to ambient 26°C. Carcass yield, organs and the internal temperature of the quail kept at 26 and 32°C are not influenced